THE EFFECTIVE RESEARCH PROCESS: UNLOCKING THE ADVANTAGES OF ETHNOGRAPHIC STRATEGIES IN THE QUALITATIVE RESEARCH METHODS - Ejimabo, Nick Obioma (European Scientific Journal, ESJ, 2015)
In doing academic and educational research activities, many researchers especially, the doctoral students find it very hard and challenging in choosing the best and appropriate research method for a particular research. While some people are overwhelmed by the plethora of research designs, many researchers still believed that it is difficult and complex in making the selection of the right research approach and methodology for any research study. This exploratory study examined the ethnographic approach in the qualitative research design as an effective process in educational research protocols. The ethnography design as one of the qualitative research methods became significantly popular in the academic globe in the 1980s as well as a useful tool for doing research related activities from the cultural and natural settings. The purpose of this investigation is focused and centered on helping the present and future doctorial students unlock the benefits of using the ethnographic strategies in the qualitative research methods to conduct their research study. Data for this study were collected from 26 present and future doctoral students from San Antonio, Texas. The findings that emerged from the data suggested that while there are some other research designs associated with the qualitative method, many doctoral students prefer to use ethnographic paradigm as the most effective and appropriate process in conducting qualitative research.